2014
DOI: 10.1370/afm.1659
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Health Records for Intervention Research: A Cluster Randomized Trial to Reduce Antibiotic Prescribing in Primary Care (eCRT Study)

Abstract: PURPOSE This study aimed to implement a point-of-care cluster randomized trial using electronic health records. We evaluated the effectiveness of electronically delivered decision support tools at reducing antibiotic prescribing for respiratory tract infections in primary care. METHODSFamily practices from England and Scotland participating in the Clinical Practice Research Datalink (CPRD) were included in the trial; 53 family practices were allocated to intervention and 51 practices were allocated to usual ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
128
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(135 citation statements)
references
References 25 publications
1
128
0
6
Order By: Relevance
“…23 For each CPRD general practice we estimated the rate of RTI consultations per 1000 registered patients, the antibiotic prescribing rate for RTI per 1000 registered patients, and the proportion (%) of RTI consultations with antibiotics prescribed. These prescribing measures were estimated on a sample of CPRD data because it was not feasible and our licence did not allow us to perform the analysis on the entire CPRD database.…”
Section: Methodsmentioning
confidence: 99%
“…23 For each CPRD general practice we estimated the rate of RTI consultations per 1000 registered patients, the antibiotic prescribing rate for RTI per 1000 registered patients, and the proportion (%) of RTI consultations with antibiotics prescribed. These prescribing measures were estimated on a sample of CPRD data because it was not feasible and our licence did not allow us to perform the analysis on the entire CPRD database.…”
Section: Methodsmentioning
confidence: 99%
“…80 We have previously conducted cluster RCTs using primary care electronic health records, with the Clinical Practice Research Datalink (CPRD) 81 as the data source. These cluster trials were in implementation research focusing on primary care management and appropriate prescribing for respiratory infections 82 and stroke secondary prevention. 83 Van Staa et al 84 reported on two pilot clinical trials to evaluate statin prescribing for CVD prevention and antibiotic prescribing for chronic obstructive pulmonary disease.…”
Section: Rapid Trials Using Electronic Health Recordsmentioning
confidence: 99%
“…The RECORD statement focuses on observational studies, as an extension to STROBE. However, increasingly, routine data are being used for research that is not observational in nature, including pragmatic randomized controlled trials, where they have the potential for great efficiency and inclusiveness . In future, the RECORD will be modified to encompass interventional studies and other research designs.…”
Section: The Record Statement – Checklist Of Items Extended From Thementioning
confidence: 99%